The occurrence of Scolymia cubensis in Brazil: revising the problem of the Caribbean solitary mussids - Neves, Elizabeth; Johnsson, Rodrigo; Sampaio, Claudio; Pichon, Michel (Zootaxa, 2006)
Identification of scleractinian corals is traditionally based upon morphological analysis of skeleton traits. However, due to the influence of the environment on coral development, and the pattern highly variable of most diagnostical characters, additional information related to anatomy of soft parts, reproductive behavior and ecological interactions have been argued to support the distinction among similar morphotypes. Caribbean and South Atlantic Scolymia comprise a small group of solitary zooxanthellate corals: Scolymia lacera, S. cubensis and S. wellsii have been far subject of taxonomical misunderstandings. Aggressive interactions bewteen S. lacera and S. cubensis were useful to validate their specific status. Nevertheless, S. wellsii has been erroneously suggested to be synonym of S. cubensis. Following Laborel, Lang and Wells’ studies, we reinforce the individuality of the Atlantic Scolymia species, confirming the occurrence of S. cubensis to Brazil. Supporting newly-reported occurrences of Caribbean species along the Brazilian littoral, this finding is likely to contribute with a new perspective to assess the ‘variability’ among scleractinian corals. A key for the identification of the Scolymia species is provided.